2017
DOI: 10.1080/13813455.2017.1347690
|View full text |Cite
|
Sign up to set email alerts
|

The G allele of MMP12 -82 A > G promoter polymorphism as a protective factor for COPD in Bulgarian population

Abstract: Chronic inflammation and remodelling of the small airways are features related to chronic obstructive pulmonary disease (COPD). In the current study, we aimed to explore the possible role of MMP12 -82 A > G (rs2276109) promoter polymorphism in the development of COPD in a population from Bulgaria (167 patients with COPD and 119 control individuals). The genotype and allele distributions differed significantly between COPD patients and controls (p = .010 and p = .043, respectively, χ test). The genotypes contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Our findings agree with previous studies reporting a lack of correlation between the MMP‐12 (–82) A/G polymorphism and the risk of COPD among Mexican, Brazilian and Russian populations, although they are discordant with data from Hunninghake et al . and Tacheva et al . indicating that the (–82) G allele associates with a reduced risk of COPD.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our findings agree with previous studies reporting a lack of correlation between the MMP‐12 (–82) A/G polymorphism and the risk of COPD among Mexican, Brazilian and Russian populations, although they are discordant with data from Hunninghake et al . and Tacheva et al . indicating that the (–82) G allele associates with a reduced risk of COPD.…”
Section: Discussionsupporting
confidence: 87%
“…and Tacheva et al30 indicating that the (-82) G allele associates with a reduced risk of COPD. The results of the present study also disagree with those of Korytina et al31 who found a significant association between the (-82) A/G variant and increased risk of chronic bronchitis.…”
mentioning
confidence: 90%
“…This allele is further associated with a reduced risk of COPD in adult smokers 137 . Although only one tendency was identified in Polish populations 130 , in Bulgaria, patients carrying genotypes with at least one copy of allele G could have a lower risk of COPD 138 .…”
Section: Genes Of Extracellular Mmps and Copdmentioning
confidence: 97%
“…All together 194 patients with COPD and 281 non-affected control individuals from the region of Stara Zagora, Bulgaria, were included in our case-control study. The including criteria for the individuals with COPD was as described previously (Tacheva et al 2017). The patients were recruited in the Clinic of Internal Medicine, University Hospital, Trakia University, Stara Zagora, Bulgaria from 2008 till 2011.…”
Section: Patients and Controlsmentioning
confidence: 99%